Long-term patient satisfaction and quality of life after breast-conserving therapy: a prospective study using the BREAST-Q - Stolpner, Ilona; Heil, Jörg; Riedel, Fabian; Wallwiener, Markus; Schäfgen, Benedikt; Feißt, Manuel; Golatta, Michael; Hennigs, André (Annals of surgical oncology, 2021)
Poor patient-reported satisfaction after breast-conserving therapy (BCT) has been associated with impaired health-related quality of life (HRQOL) and subsequent depression in retrospective analysis. This prospective cohort study aimed to assess the HRQOL of patients who have undergone BCT using the BREAST-Q, and to identify clinical risk factors for lower patient satisfaction.